IMPROVING THE QUALITY OF EDUCATION THROUGH INNOVATIONS IN EDUCATION - Khashimova Abitovna, Naima (THE INNOVATION ECONOMY, 2025)
This article is aimed at analyzing innovative approaches and methods in the field of education. It discusses effective methods of improving quality through the use of innovations in education, technological opportunities and global trends. Innovative approaches are of great importance not only for improving the learning process of students, but also for modernizing the general education system. The article provides detailed information on the advantages, problems and future development prospects of introducing innovations in education.